Transforming Children's Attitudes and Knowledge towards Vegetable Consumption through Think Pair Share-Based Health Education - Puastiningsih, Sri; Sahlan, Sahlan (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The aim of this study was to analyze the effect of implementing health education with the think pair share learning model on the knowledge and attitudes of school-age children regarding vegetable consumption. Methodology: This study used a pre-experimental design with a one-group pre-post test approach. A sample of 40 fourth-grade students was drawn using a total sampling technique. The independent variable was health education using the Think Pair Share model, while the dependent variables were knowledge and attitudes. Data analysis used the Wilcoxon Sign Rank Test with α≤0.05. Main Findings: The results of the Wilcoxon Sign Rank Test statistical test show that health education with the think pair share learning model can influence children's knowledge (p=0.000) and attitudes (p=0.000). Novelty/Originality of this study: The novelty of this research lies in the application of the Think Pair Share learning model in health education to improve school-age children's knowledge and attitudes toward vegetable consumption. This approach has not been widely used in the context of child nutrition, thus providing an innovative contribution to effective and participatory health education methods.